Providing Treatment in a Prison-Based Therapeutic Community for Those Who Have Committed Sexual Offences - Akerman, Geraldine (International journal of offender therapy and comparative criminology, 2021)
This article explores some of the difficulties inherent in managing risk in those who have committed sexual or other violent offences and how this may impact on their ability to re-integrate into the community. It discusses the work undertaken at HMP Grendon, a prison-based therapeutic community (TC), to address these difficulties and help residents develop a pro-social lifestyle starting in custody and continuing on release. The article aims to describe how the TC model offers a containing and adaptive environment, and how this can provide opportunities to address offence-related behaviour, which is not always possible in other prison settings. Furthermore, it describes some of the difficulties inherent in undertaking work of this nature, in the need for an accurate understanding of the relevant areas of risk, and the tensions developing a therapeutic relationship with individuals with complex needs. Methods of assessment of risk and need are discussed, and how they are used in a collaborative manner to have the most accurate picture of what will help residents to maintain their pro-social lifestyle on release.